The Role of Law Enforcement in Ensuring the Rights of Citizens - BAKAIANOVA, Nana M.; KRYZHANOVSKA, Olena V.; KUBAIENKO, Andrii V. (Journal of Advanced Research in Law and Economics, 2019)
The paper investigates human and citizen rights in Ukraine, their reflection in modern international regulations, in the laws of Ukraine. The features of the implementation of law enforcement in modern conditions are considered through the lens of the experience of other countries. The possibility of reforming the law enforcement system for improving its efficiency was analyzed. To achieve the purpose and form conclusions, various criteria for the effectiveness of law enforcement were considered. Particular importance in solving this issue was given to the analysis of foreign experience. The experience of other countries and world communities will allow to implement the best methods of law enforcement in Ukraine and improve its efficiency, paying particular attention to the rights of citizens even in high alert conditions (for example, in emergency situations, when human rights are minimized). Two leading approaches were used in the study: general theoretical and general historical. They helped identify the strengths and weaknesses of the current system in Ukraine and formulate specific positions for improving the activities of law enforcement agencies of Ukraine in protecting citizens' rights.